PERAN MEDIASI KEPUASAN KERJA PADA PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PERSEROAN TERBATAS BANK PERKREDITAN RAKYAT SYARIAH SUKOWATI SRAGEN - Triatmojo, Thoriq Fajar; Suseno, Y. Djoko; Sutarno, Sutarno (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
The purpose of this study was to analyze the significance of the effect of leadership style and work motivation on job satisfaction and analyze the mediating role of work satisfaction in affect leadership style and work motivation on employee performance. This type of research is survey research. The study population was 85 employees of PT. BPR Syariah Sukowati Sragen and all of them are sampled by census technique. Data sources used primary data and secondary data. Methods of data collection used questionnaires and literature study. Data analysis techniques used path analysis. The results showed that the leadership style has a significant effect on the work satisfaction. Work motivation has a significant effect on work satisfaction. Leadership style has a significant effect on the employee performance. Work motivation has a significant effect on the employee performance. Work motivation has a significant effect on the employee performance. Job satisfaction mediates the affect of the leadership style on the employee performance. Work satisfaction mediates the affect of work motivation on employee performance.